Are there differences in efficacy and safety between local and imported direct-acting antiviral agents for hepatitis C in China? - Zhitao Wang; Youbing Ran; Yihan Fu; Jing Sun; Yuanli Liu (Infectious Diseases of Poverty)
Abstract Background Despite price advantages, local direct-acting antiviral agents (DAAs) for hepatitis C (hep C) have not been widely used in China compared with the imported ones. There is no evidence on their relative efficacy and safety, nor whether the small market share of local DAAs was attributable to the potential differences. Methods This study systematically evaluated the efficacy and safety evidence of 5 local and 6 imported DAAs with valid Chinese registration numbers as of January 25, 2024. Meta-analyses, subgroup analyses and meta-regressions were performed to synthesize evidence and compared the outcomes by using the random-effects empirical Bayes model. Results Nineteen randomized controlled trials and 82 single-arm trials (SATs) were included. The results demonstrated no statistically significant difference in 12-week sustained virological response [0.97, (95% confidence interval (CI) 0.95, 0.99) vs 0.96, (95% CI: 0.94, 0.98), P = 0.21], relapse [0.02, (95% CI: 0.01, 0.04) vs 0.02, (95% CI: 0.01, 0.03), P = 0.65], virological breakthrough [0.003, (95% CI: < 0.001, 0.02) vs 0.0000002, (95% CI: < 0.001, 0.0006), P = 0.51] and serious adverse events (SAEs) [0.04, (95% CI: 0.03, 0.06) vs 0.03, (95% CI: 0.02, 0.03), P = 0.12] between local and imported DAAs. By controlling for ethnicities of patients in multiple meta-regression, the local DAAs had a 33.7% higher rate of adverse events (AEs) [0.337, (95% CI: 0.188, 0.486), P < 0.001]. No statistically significant difference was found in the interaction test between local and imported pan-genotypic DAAs regarding the rate of AEs [0.72, (95% CI: 0.64, 0.79) vs 0.73, (95% CI: 0.65, 0.50), P = 0.81]. Conclusions Current evidence demonstrates no statistically significant differences in efficacy and SAEs between local and imported DAAs. Given that simplified pan-genotypic DAA regimens are now standard care, local pan-genotypic DAAs hold potential to increase hepatitis C virus treatment rates in China. It is critical for local DAA developers to generate more evidence with expanded patient population in terms of age, treatment experience and genotype of hepatitis C virus, conducting head-to-head studies directly comparing the efficacy and safety. Clinical and policy decision-making should be adaptive and evolve as new evidence is generated. Graphical Abstract